Utilizing Global Method to Improve Reading Comprehension of EFL Students - Supuinda, Arum Yudyah A; Anggreni, Afrillia; Marhum, Mochtar; Darmawan, Darmawan (Universitas Pahlawan Tuanku Tambusai, 2025)
Comprehending reading text in many genres is one of the main goals in learning English at the Junior High School level. Many innovative methods have been adapted and implemented by numerous scholars to improve this receptive skill. Thus, this study exposes the effectiveness of the Global Method to improve reading comprehension of eighth-grade students at SMP Negeri 1 Sigi and focuses on Narrative text. A quasi-experimental design was utilized involving two classes: an experimental class taught using the Global Method and a control class taught using conventional methods. A total of 46 students participated in this study. Both groups were given pre-tests and post-tests to measure their reading comprehension before and after the treatment. Paired sample t-tests and independent sample t-tests are applied to determine the significance differences between the two groups. The results present that the experimental class achieves a significant improvement in reading comprehension, with the mean score increasing from 66.91 in the pre-test to 87.91 in the post-test. In contrast, the control class points out a smaller improvement, with mean scores rising from 61.70 to 73.35. Statistical analysis confirmed that the Global Method has a significant positive effect on students’ reading comprehension (the p-value 0.001 lower than 0,05). Therefore, the Global Method is more effective than conventional teaching methods in enhancing students’ ability to understand narrative texts. It is recommended that English teachers incorporate this method into their instructional reading practices to support students’ comprehension development.